Death and the Machine Intersections of Mortality and Robotics - Lyons, Siobhan (Springer Singapore, 2018)
This books challenges conventional notions of biological life and death in the area of robotics, discussing issues such as machine consciousness, autonomous AI, and representations of robots in popular culture. Using philosophical approaches alongside scientific theory, this book offers a compelling critique on the changing nature of both humanity and biological death in an increasingly technological world.